STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGUATAN KEMITRAAN DUNIA USAHA DAN DUNIA INDUSTRI (DU/DI) UNTUK PENINGKATAN MUTU PRAKERIN BERBASIS PEMBELAJARAN BERMAKNA - Monika Simon Kendek; Yulius Mataputun; Albaiti Albaiti; Diki Kurniawan; Monika Gultom; Kusdianto Kusdianto (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The phenomenon of skills mismatch that triggers high rates of educational decline and sociocultural challenges in the Central Papua region is the background of this research. This problem requires innovative managerial intervention from school leaders to optimize the implementation of work practices. The focus of this research is to analyze the leadership strategy of the principal in the partnership between the Business World and the World of Industry (DU/DI) to improve the quality of Industrial Work Practice (Prakerin) based on Meaningful Learning at SMKS Tunas Bangsa Pariwisata Mimika. The steps of this qualitative descriptive research with a case study design were designed through the stages of field exploration, original data collection, and analysis of the interactive model of Miles, Huberman, and Saldana which includes data reduction, data presentation, and drawing conclusions. Primary data sources include in-depth interviews with 12 key informants as well as participatory observation and formal documentation studies. The findings indicate that the principal integrates the Adaptive Contextual Leadership model with the Link and Match policy through the alignment of the tourism curriculum, the use of a physical objective assessment format by industry mentors, and the consistent implementation of organizer advancement. The main conclusion emphasizes that this adaptive-contextual leadership strategy that focuses on strengthening intellectual, emotional, and spiritual character has proven to be very effective in transforming the quality of Prakerin, boosting knowledge retention, and building a sustainable reputation and trust in the industry. ABSTRAK Fenomena skills mismatch yang memicu tingginya angka pengangguran lulusan vokasi serta tantangan sosiokultural di wilayah Papua Tengah melatarbelakangi penelitian ini. Masalah tersebut menuntut adanya intervensi manajerial yang inovatif dari figur pimpinan sekolah guna mengoptimalkan pelaksanaan praktik kerja. Fokus penelitian ini adalah menganalisis strategi kepemimpinan kepala sekolah dalam penguatan kemitraan Dunia Usaha dan Dunia Industri (DU/DI) untuk meningkatkan mutu Praktik Kerja Industri (Prakerin) berbasis Pembelajaran Bermakna di SMKS Tunas Bangsa Pariwisata Mimika. Langkah-langkah penelitian deskriptif kualitatif dengan desain studi kasus ini dirancang melalui tahapan eksplorasi lapangan, pengumpulan data orisinal, serta analisis interaktif model Miles, Huberman, dan Saldana yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Sumber data primer melibatkan wawancara mendalam terhadap 12 informan kunci beserta observasi partisipatif dan studi dokumentasi formal. Hasil temuan menunjukkan bahwa kepala sekolah mengintegrasikan model Adaptive Contextual Leadership dengan kebijakan Link and Match melalui penyelarasan kurikulum pariwisata, pemanfaatan format penilaian fisik objektif oleh mentor industri, serta penerapan advance organizer secara konsisten. Simpulan utama menegaskan bahwa strategi kepemimpinan adaptif-kontekstual yang berfokus pada penguatan karakter intelektual, emosional, dan spiritual ini terbukti sangat efektif mentransformasi mutu Prakerin, mendongkrak retensi pengetahuan, serta membangun reputasi dan kepercayaan industri berkelanjutan.